From founders to firm: Examining the retention of founder-CEO social capital in venture-backed firms - Bret R. Fund (The Journal of Entrepreneurial Finance (JEF), 2016)
This paper examines how organizations protect themselves from the negative social and economic consequences associated with the loss of a key member and their social capital. Drawing on the social capital and upper echelons literatures, the author(s) hypothesize that social capital can be institutionalized. The corresponding hypotheses are tested on a sample of 125 venture-backed software firms and the results demonstrate that the institutionalization of a founder-CEO's social capital leads to better performance for a firm. The results provide a basis for understanding how social mechanisms influence economic organization as well as succession and compensation in a new venture context.
Keywords: 650; founder-ceo transitions; venture capital; startups; social capital & entrepreneurial leadership